Dwelling Telling: Literalness and Ontology - Beeman, Chris; Blenkinsop, Sean (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2008)
At a certain time during the filming of Daki Menan I began to question my own readiness to make metaphor of the experience of others. I began, instead, to regard the literal words of the Temi-Augama Anishinaabe elders with whom I was working as accurate representations of what they thought, especially the way they thought about how the world worked. But if this move to literalism were justified, I had to acknowledge that what I thought to be the parameters of being would change. This paper is about that change, as mediated through the concept of attentive receptivity.